PENDEKATAN DIMENSI KEPUASAN EKSTRINSIK DAN PENGARUHNYA TERHADAP KOMITMEN DAN PERILAKU ORGANIZATIONAL CITIZENSHIP KARYAWAN OPERASIONAL HOTEL BINTANG LIMA DI NUSA DUA BALI (Upaya Tingkatkan Daya Saing Sumberdaya Manusia Lokal Dalam Ekowisata) - Udiyana, Ida Bagus Gede; Wignjohartojo, Parwoto; Sulasmi, Siti (Bumi Lestari; Vol 12 No 1 (2012), 2012)
The aims of the study is to analyze and to find the existence of satisfaction to the commitment and organizational citizenship behavior, and to develop the theory of Al Busaidi and Kuehn (2002), Dumler (1997), and Organ and Ryan (1995) that OCB is influenced by an extrinsic satisfaction and commitment. The subject of the research is the five stars hotels at Nusa Dua Bali, the object of the research is using three variables consist of extrinsic satisfaction as independent variable, one commitment variable as intervening variable, and organizational citizenship behavior as dependent variable. Respondent are the Hindu religion the hotel operational employees of 198 samples. The method of collecting data is using simple random sampling method with proportional allocation. The data analyzed in this research is using structural equation modeling (SEM) analysis technique, which is using AMOS 7 program (Analysis Structure) and SPSS 13.0 version. This research has found an expansion theory of Al Busaidi and Kuehn (2002), Dumler (1997), and Organ and Ryan (1995) that OCB is influenced by extrinsic satisfaction consist of reward policy dimension, job environment policy/ job situation and job environment. Furthermore, this research has found a theory that the main variable that is causing the appearance of organizational citizenship behavior are extrinsic satisfaction and commitment or OCB function of an extrinsic satisfaction and commitment. From this research can also be found that extrinsic satisfaction can be devided into an intrinsic satisfaction and extrinsic satisfaction.
Keywords: job environment, extrinsic satisfaction, commitment and organization citizenship behavior